Organizational communication and innovation in micro and small companies: a study on the application of the Innovation Radar - Macedo, Aline Mariano [UNESP]; Porém, Maria Eugênia [UNESP]; Andrelo, Roseane [UNESP] (University of Minho, 2014)
This paper is a study on corporate communication and the ability to innovate in small businesses. The guiding question seeks to respond whether organizational communication is able to make progress and / or support innovation in micro and small companies, and the main objective is to analyze the relationship between innovation and organizational communication. It was applied the case study method and document research for interpreting a diagnosis instru- ment called “Innovation Radar” in a small business company located in the countryside of São Paulo state. The diagnosis is made based on assessment dimensions aimed at checking the maturity and the degree of innovation in micro and small companies. By evaluating these di- mensions it was possible to build analytical frameworks and highlight the influence of corporate communication in promoting innovation. The results indicate that every dimension of the “In- novation Radar” can improve their performance by means of corporate communication.
Keywords: Corporate communication; Innovation; Micro and small companies; Innovatin Radar